2021
DOI: 10.1371/journal.pone.0245826
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ experiences and perceptions of Guillain-Barré syndrome: A systematic review and meta-synthesis of qualitative research

Abstract: Background Guillain-Barré syndrome (GBS) is an immune-mediated polyradiculoneuropathy, with an incidence of 1-2/100,000 per year. Its severity is variable, ranging from very mild cases with brief weakness to severe paralysis, leading to inability to breathe independently, or even death. Currently there is limited evidence exploring the experiences of GBS patients. The aim of this study was to review patients’ experiences and perceptions of GBS and its variants at diagnosis, discharge and during recovery, by co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 22 publications
1
10
0
1
Order By: Relevance
“…The questionnaire showed reliability as excellent for symptoms, good for information provided and factors affecting recovery and acceptable for care received and symptom subscales. Physical, psychological and social factors were associated with recovery, and concordance with recent studies 11,13 supports construct validity.…”
Section: Main Findingssupporting
confidence: 86%
See 4 more Smart Citations
“…The questionnaire showed reliability as excellent for symptoms, good for information provided and factors affecting recovery and acceptable for care received and symptom subscales. Physical, psychological and social factors were associated with recovery, and concordance with recent studies 11,13 supports construct validity.…”
Section: Main Findingssupporting
confidence: 86%
“…10 A recent systematic review and metasynthesis of qualitative studies of people with GBS showed the complexity of experience of the illness, its care and rehabilitation from illness onset to hospitalisation with acute symptoms, recovery and adjustment in the case of longer-term problems. 11 This and other studies of patient-reported experiences of neurological conditions have identified common factors associated with care quality. 12 A further qualitative study exploring those factors associated with recovery demonstrated the importance of early diagnosis, positive experiences of inpatient care, active support for recovery and good communication and information provision.…”
Section: Introductionmentioning
confidence: 72%
See 3 more Smart Citations